2017
DOI: 10.1093/intqhc/mzx056
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned for reducing the negative impact of adverse events on patients, health professionals and healthcare organizations

Abstract: Recommendations preventing aftermath of AEs have been identified. These have been designed for the hospital and the primary care settings; to cope with patient's emotions and for tacking the impact of AE in the second victim's colleagues. Its systematic use should help for the establishment of organizational action plans after an AE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 77 publications
2
61
0
5
Order By: Relevance
“…It has been reported that a second victim may be affected to varying degrees in terms of physical health, psychological health, professional efficacy and other aspects and that PSIs can even reoccur (Cabilan & Kynoch, 2017; Mira, Carrillo, et al, 2017; Mira, Lorenzo, et al, 2017; Pratt & Jachna, 2015), which deserves the attention of managers in the medical field. Scott (Scott et al, 2009) believes a post‐event trajectory is predictable, and the following six stages are identified: chaos and accident response, intrusive reflections, restoring personal integrity, enduring the inquisition, obtaining emotional first aid and moving on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that a second victim may be affected to varying degrees in terms of physical health, psychological health, professional efficacy and other aspects and that PSIs can even reoccur (Cabilan & Kynoch, 2017; Mira, Carrillo, et al, 2017; Mira, Lorenzo, et al, 2017; Pratt & Jachna, 2015), which deserves the attention of managers in the medical field. Scott (Scott et al, 2009) believes a post‐event trajectory is predictable, and the following six stages are identified: chaos and accident response, intrusive reflections, restoring personal integrity, enduring the inquisition, obtaining emotional first aid and moving on.…”
Section: Introductionmentioning
confidence: 99%
“…Scott (Scott et al, 2009) believes a post‐event trajectory is predictable, and the following six stages are identified: chaos and accident response, intrusive reflections, restoring personal integrity, enduring the inquisition, obtaining emotional first aid and moving on. In addition, assistance for second victims is of great significance, and discussing the event with colleagues, feeling respect and empathy from others and being supported by institution are helpful in coping with the emotional impact (Dukhanin et al, 2018; Edrees et al, 2016; Mira, Carrillo, et al, 2017; Mira, Lorenzo, et al, 2017). However, the literature has also emphasized that thus far, such support is limited in health systems due to the failure to identify potential second victims, insufficient support interventions and the lack of a patient safety culture (Quillivan et al, 2016; Stewart et al, 2015; Tsao & Browne, 2015; Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These data contrast with those found in other countries that have made a greater effort to replace the punitive culture after the error. For example, the number of hospitals that do have support programs for second victims is notably higher in the USA [24] (74%) and the Netherlands [6] (30%). However, they tend to coincide with the results of the study carried out in Spain in which around 70% of patients who suffered an AE did not receive adequate information about the incident or to obtain fair compensation.…”
Section: Discussionmentioning
confidence: 99%
“…It is more difficult for patients suffering from AEs to receive information about what happened and for their right to fair compensation to be respected. On the other hand, professionals involved in safety incidents suffered by patients (and their families) often find it difficult to discuss what happened with their colleagues and middle-managers, question their own professional capacity and ultimately make wrong decisions more easily [6].…”
Section: Aftermatch Of Safety Eventsmentioning
confidence: 99%
“…The risk factors for occupational injury can be attributed to an interaction between characteristics of the worker and the patient, and the workplace [9,10]. Adverse events may affect not only HCWs but also patients, and in addition may have a negative impact on relatives and health care organizations, all considered as a signi cant problem [11,12]. Approximately 10-15% of patients are affected by an adverse event during their hospital stay, and a substantial part of these events are considered preventable [13,14].…”
Section: Introductionmentioning
confidence: 99%